Mid-upper arm circumference as an indicator of nutritional status improvement in children aged 6-59 months with severe acute malnutrition - Putri, Trivani; Prasetyadi, Yosafat Lambang; Ibrahim, Naufal Arkan Abiyyu; Hafifah, Cut Nurul (Paediatrica Indonesiana, 2024)
Background The prevalence of severe acute malnutrition (SAM) in Indonesia remains high, especially in children with pre-existing chronic disease. These children often present with conditions that could interfere with weight measurements, such as edema or organomegaly. Mid-upper arm circumference (MUAC) is a potential indicator of nutritional status improvement. Objective To analyze the correlation between MUAC and body weight as parameters for nutritional improvement in children with SAM. Methods We performed registry analysis of patients admitted to the Pediatric Ward, Cipto Mangunkusumo Hospital, Jakarta, Indonesia from November 2016 to December 2020. We included children aged 6-59 months who were severely wasted (z-score <-3 on the WHO weight-for-height growth chart), had no conditions that could alter weight measurement, and had a 7-day minimum hospital stay. Patients with missing body weight and/or MUAC data were excluded. MUAC and weight increment between admission and discharge were analyzed using bivariate correlation and linear regression analyses. Results Out of 4,746 pediatric inpatients, 1,996 presented with SAM. Of these, 124 were eligible for analysis. Subjects’ median age was 18 (IQR 11-32) months and median length of stay was 16 days (IQR 9-29 days). Weight increment (g/kg/day) and MUAC increment (mm/day) were independently and significantly correlated (P<0.001; Spearman’s rho=0.414). An adequate weight increment of 5-10 g/kg/day was equivalent to a MUAC increment of 0.319-0.439 mm/day (P<0.001; R=0.374). Conclusion MUAC increment has a moderate positive correlated with weight increment. MUAC is a useful parameter of nutritional status improvement in SAM patients, especially in patients with conditions that could interfere with weight measurement.